The first movements of the child the mental structures and dyadic relationship with the mother - Rosa, Sgambelluri (Advances in Social Sciences Research Journal, 2016)
Mother and child in their act and react, constitute a place in which the child lays the foundations of one of the most developed areas of its competence: reading and interpretation of signals and emotional expressions of other people’s behaviour. Several studies have shown that the child is provided with a social awareness at birth, characterized by a preference for faces, direct gaze and imitation, a true “pre-adaptation” which enables to social relationship and emerging both within the ability of expression and organization behavior and in the perceptual ability.